Influence of rotational speed on the cyclic fatigue of Mtwo instruments. (31st August 2013) - Pedullà, E.; Plotino, G.; Grande, N. M.; Scibilia, M.; Pappalardo, A.; Malagnino, V. A.; Rapisarda, E.
Abstract Aim To evaluate the effect of rotational speed on cyclic fatigue of Mtwo nickel–titanium files. Methodology A total of 120 new Mtwo rotary instruments sizes 10, 0.04 taper; 15, 0.05 taper; 20, 0.05 taper; and 25, 0.06 taper were randomly divided into three groups on the basis of the rotational speed used to shape nine standardized simulated canals: group A = 350 rpm; group B = 250 rpm; group C = 150 rpm. Each group consisted of 40 instruments, 10 for every size. The average preparation time (in seconds) and the average correlated numbers of cycles to instrument (NCI) the nine standardized canals were recorded for each file. The resistance to cyclic fatigue was determined by counting numbers of cycles to failure (NCF) with a rotational speed of 300 rpm in a 60° curve with a 5‐mm radius. Data were analysed by two‐way anova. Results Preparation time was significantly longer at 150 rpm than at 250 or 350 rpm. The average number of cycles needed for each file to instrument nine standardized canals was significantly higher at 350 and 250 rpm, than at 150 rpm. There were no significant differences in the NCF (P > 0.05) between A, B and C groups for instruments of the same size. Conclusions Speed did not affect the cyclic fatigue of Mtwo instruments with the same size and taper. Preparation time was shorter at 350 or 250 rpm rather than at 150 rpm. However, there was no significant difference between 350 and 250 rpm rotational speed, neither in the preparation time of simulated canals nor in the resistance to fatigue fracture.